Análisis De La Efectividad De Las Acciones De Comunicación De Crisis De La Alcaldia De Calarcá En Relación Con Lo Presentado En El Diario La Crónica Del Quindio (2013)
Crisis communication is consider as a set of communication techniques to manage crisis situations, also it helps to find benefits to prevent and minimize unfavorable situations for the organization.  Crises are not phenomenon sporadic, isolated or infrequent, it is within the logic of the market, the behavior of individuals and the performance of organizations. Crisis are unexpected events, sudden and dangerous. Furthermore crises may generate tension to the stakeholders ( internal and external) in some cases it can cause destabilization to the organization, sometimes the members of the organization can be more concerned to resolve the conflict generated for the crisis than continuing their normal activity in the organization.  Currently the main objective of the Crisis Communication's is research to find benefits that can help to minimize adverse situations for the organization, this is being a crucial point for the business sector.